Faktor risiko paritas terhadap kejadian preeklampsia - eklampsian pada ibu bersalin - Fitri Nur Hidayah; Sujiyatini Sujiyatini; Nur Djanah (Jurnal Kesehatan Ibu dan Anak, 2014)
MMR is the highest in the province of Yogyakarta is located in Kulon Progo Regency which 167.34/100,000 live births,with the main causes of preeklampsia-eklampsia. Some factors that are identified can trigger events preeklampsia-eklampsia i.e., parity, age and obesity. This research aims to find out whether parity as the largest risk factor against preeklampsia-eklampsia on the mother's maternity RSUD Wates in 2011. Type of the research was an observational usingCase Control approach. The Data used are secondary data with nominal scale. Total sample 294 consists of 147case group and 147 control group with systematic random sampling. Analysis using Chi Square test with a confidence level of 95%and multivariate logistic regression analysis. The resuits showed the incident preeklampsia-eklampsia more at birthing mothers with high risk parity (< 2 and > 4) asmuch as 75,51%. Chi square analysis showedthe p-value of <0.05, OR 3.87 ,CI 2,30-6,61, with multivariate logistic regression analysis regression coefficient obtained parity 1.5408, age 1.2678, the incidence of obesity 0.9040. Summary of parity is the biggest risk factor against incidentpreeklampsia-eklampsia.High risk parity (<2 and >4) larger 3,87 risky going preeklampsia-eklampsia compared tonot high risk parity (2-4)